2018
DOI: 10.1038/s41598-018-31286-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Radiation Hardness of Silicon Photonic Sensors

Abstract: In recent years, silicon photonic platforms have undergone rapid maturation enabling not only optical communication but complex scientific experiments ranging from sensors applications to fundamental physics investigations. There is considerable interest in deploying photonics-based communication and science instruments in harsh environments such as outer space, where radiation damage is a significant concern. In this study, we have examined the impact of cobalt-60 γ-ray radiation up to 1 megagray (MGy) absorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 25 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The latter in thermometers is usually referred to as robustness-a sought-after quality in the research and development stage. For example, Ahmed et al [34] recently demonstrated that silicon photonic thermometers can withstand up to 1 megagray of γ-radiation without showing any changes in device characteristics such as peak center, peak width, free spectral range, and temperature sensitivity. • Construction (or packaging) is one of the key factors in the development of thermometers as there exist two conflicting requirements: exposing the sensor to a temperature stimulus, while protecting it (and its interface electronics) from everything else (typically referred to as environmental damage).…”
Section: Performance Metrics For Selecting An Emerging Temperature Se...mentioning
confidence: 99%
“…The latter in thermometers is usually referred to as robustness-a sought-after quality in the research and development stage. For example, Ahmed et al [34] recently demonstrated that silicon photonic thermometers can withstand up to 1 megagray of γ-radiation without showing any changes in device characteristics such as peak center, peak width, free spectral range, and temperature sensitivity. • Construction (or packaging) is one of the key factors in the development of thermometers as there exist two conflicting requirements: exposing the sensor to a temperature stimulus, while protecting it (and its interface electronics) from everything else (typically referred to as environmental damage).…”
Section: Performance Metrics For Selecting An Emerging Temperature Se...mentioning
confidence: 99%
“…Space radiation is composed of two primary groups: cosmic rays of electromagnetic wave packets and radiation particles (protons, electrons, and heavy ions) reaching extremely high kinetic energy (16). Ground radiation tests of Si PICs have been focusing on single-frequency γray (10 6 eV) (19)(20)(21)(22) and x-ray (10 4 eV) exposure of passive devices (19,(23)(24)(25), with dosage equivalent to 10 3 years of exposure on low earth orbit (LEO). The high dosage of such electromagnetic radiation results in primary TIDs in Si-on-insulator (SOI) substrate and reduces the tuning efficiency (23,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Miniaturization, reduced power consumption and tolerance to mechanical stimulus of photonic sensors and optoelectronic devices based on a-SiO 2 or a-Si 3 N 4 have motivated their use in ion accelerators, nuclear power plants or aerospace applications [11,12]. However, their performance in ionizing radiation environments can degrade due to a change in density, refractive index or covalent bond breaking [11,13] that leads to optical loses [14] and current leakage [12]. a-SiO 2 has been studied under a wide range of radiation conditions, and to a lesser extent a-Si 3 N 4 , yet it appears that a-Si 3 N 4 is more radiation resistant than a-SiO 2 (as discussed in the introductory part in [15]).…”
Section: Introductionmentioning
confidence: 99%